Magnetic structure and phase transition of Ni2Mn1.48Sb0.52 magnetic shape memory compound. (15th April 2016) - Yang, Y.B.; Liu, S.Q.; Zhao, H.; Yang, W.Y.; Wu, R.; Huang, Q.Z.; Zhou, D.; Du, H.L.; Wang, C.S.; Yang, Y.C.; Xu, H.; Zhu, J.L.; et al.
Abstract: A comprehensive study of the structural and magnetic properties of the Ni2 Mn1.48 Sb0.52 compound is presented using neutron diffraction and magnetic measurements. It is found that Mn atoms on 4a and 4b sites are ferrimagnetic coupled in the austenitic phase. At 300 K, the magnetic moments of Mn (4a) and Mn (4b) are determined to be 2.72(3) μ B and − 2.67(5) μ B, respectively. From 260 K to 4 K, the compound is in martensite phase and the magnetic moments of Mn (2a), Mn (2f), Mn (2b), Mn (2e) at 4 K are 2.2(5) μ B, 2.3(5) μ B, − 2.1(5) μ B, and − 2.6(5) μ B, respectively. Graphical abstract: